(3GdJNWjW GdGOGQjs - (3MSGe(B, (3GdYQHjs ((3YeGf(B:s (3OGQ GSGeI(B,s, 2010)
(3GdJNWjW (B: (3Gdeaghe , GdfTCI , GdGSHGH , CgejI GdJNWjW GdGOGQj , CfhGY GdJNWjW h JaGUjd GdNWW ,eQGMd GdJNWjW GdGOGQj GdfGLM , GdJNWjW h EOGQI GdhbJ , GdJNWjW h YedjI GdJaGhV , GdJNWjW h EOGQI GdGfJGL h GdYedjGJ , GdJNWjW h EOGQI GdLhOI GdTGedI , GdJNWjW h GdJShjb h GdGSJKeGQ , GdJNWjW h EOGQI GdGReGJ h GdGSJKeGQ(B.s
(3eQGLY U(B.254s
Keywords: (3EOGQI GdGYeGds; (3GdJNWjWs; (3GdJNWjW GdGOGQjs